Social Entrepreneurship in Sub-Saharan Africa - (:unkn) unknown (My University, 2015)
Responding to calls for a better understanding of the relationship between social enterprises and their environments, this article focuses on contextual influences on social entrepreneurship in sub-Saharan Africa. We identify four predominantly African contextual dimensions (acute poverty, informality, colonial history, and ethnic group identity) and explore their influence on the way social ventures perceive themselves and on their choice of activities. Our empirical study of 384 social enterprises from 19 sub-Saharan African countries suggests that ethnic group identity and acute poverty levels influence both self-perception and activity choices, the country's colonial history influences only self-perception, and informality has no significant influence on either. These findings point to the need to consider both self-perception and the choice of activities in defining social entrepreneurship. Our study also highlights the importance of African contextual dimensions for understanding social entrepreneurship, and underlines the added value of incorporating insights from African data into management research more broadly.
Keywords: African Research